PENGARUH CUSTOMER VALUE TERHADAP KEPUTUSAN MENGGUNAKAN MEETING PACKAGE DI GOLDEN FLOWER HOTEL BANDUNG (Survei Pada Tamu Bisnis di Golden Flower Hotel Bandung) - Mustika, Gina Anggina; Andari, Rini (THE Journal : Tourism and Hospitality Essentials Journal, 2015)
The development of the tourism sector in Indonesia has increasingly growth to the better way, for example MICE (meeting incentive, convention, and axibition). MICE is a part of the tourism industry today. Golden Flower Hotel Bandung is a four stars hotel in Bandung that provides a place to host MICE, with the hotel’s main goal is to get the value or positive perception from target business with appropriate targets. In 2013 Golden Flower Hotel Bandung meeting events decreased by 1,9%. The aim of this study was to obtain an overview of customer value and the decision to use meeting package and the influence on the decision to use meeting package at Golden Flower Hotel Bandung. This research used customer value as variables (X) which consist of emotional value, social value, quality/performance value and price/value of money. According to Sweeney and Soutar (Gery 2010:8), the dependent variable (Y) is the decision to use meeting package. This type of research is descriptive verification, and the using method was a survey with a systematic of random sampling, and the numbers are 50 companies as business guests at Golden Flower Hotel Bandung. For the data analysis technique and hypothesis testing, multiple regression technique was used in this research. The results showed that the sub variable social value has the highest influence towards the decision to use meeting package, because it has given good service to the guest’s business so they got memorable experience and has a value / positive perception about the Golden Flower Hotel Bandung.